PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN KEMAMPUAN PROFESIONAL GURU TERHADAP MUTU PROSES PEMBELAJARAN (STUDI KASUS DI SEKOLAH DASAR KECAMATAN CIKONENG, CIAMIS) - Desi Nurani (Wahana Pendidikan, 2021)
The study aims to analyze the influence of headmaster academic supervision towards teacher profesionalism and its relation to learning process quality at elementary schools in Indonesia. The study assumes that headmaster academic supervision gives effects on teacher professionalism and that kind of well-supervised teacher professional best practices will consequently affect learning process quality. The method used in this study is descriptive method with a quantitative approach. Totally taken 30 elementary school headmasters and elementary school teachers randomly selected in this case study were 155 people. Questionnaires and interviews were intended to investigate the subjects’ points of views about academic supervision and teacher professionalism and its relation to learning process quality. Descriptive analysis uses a Weighted Means Scored and hypothesis analysis using SPSS. Professional indicators as reflected in teaching documents such lesson plans help the study figure out their real teacher competence. Quantitative analysis using SPSS indicated that the school principal's academic supervision had a positive and significant influence on the ability of professional teachers with a low category, and the teacher's professional ability had a positive and significant influence on the learning process with a low category. The study recommend that the teachers increase their professionalism in teaching specifically in enhancing interaction with students. Further study should focus on how principals follow up their supervision results to increase teaching process quality. Keywords:   Headmaster Academic Supervision, Learning Process Quality, Teacher Profesionalism